Rapid Surface Lowering of Benito Glacier, Northern Patagonian Icefield - Ryan, Jonathan C.; Sessions, Martin; Wilson, Ryan; Wündrich, Olaf; Hubbard, Alun (Frontiers in Earth Science, 2018)
The Patagonian Icefields, which straddle the Andes below 46°S, are one of the most sensitive ice masses to climate change. However, recent mass loss from the icefields, along with its spatial and temporal variability, is not well constrained. Here we determine surface elevation changes of Benito Glacier, a 163 km2 outlet glacier draining the western flank of the North Patagonian Icefield, using a combination of field and satellite-derived elevation data acquired between 1973 and 2017. Our results demonstrate that, just below the equilibrium line, the glacier dramatically thinned by 139 m in the past 44 years, equivalent to a mean rate of 3.2 ± 0.2 m a-1. However, surface lowering was temporally variable, characterized by a hiatus between 2000 and 2013, and a subsequent increase up to 7.7 ± 3.0 m a-1 between 2013 and 2017. Analysis of Benito Glacier’s flow regime throughout the period indicates that the observed surface lowering was caused by negative surface mass balance, rather than dynamic thinning. The high rate of surface lowering observed over the past half a decade highlights the extreme sensitivity of mid-latitude glaciers to recent atmospheric forcing.